Development of Taksonify Mobile Application for Learning Biological Taxonomy with Gamification and Computer Vision - Muhammad Haulul Azkiyaa; Alfian Akbar Gozali; Raja Nur Dania binti Raja Arif Shah (Biosaintifika: Journal of Biology & Biology Education, 2026)
Taxonomy and scientific names are the most important things that make up the foundation of biology education at the secondary level. But a lot of students have trouble with these subjects because of the old-fashioned way of teaching and all the Latin words. Traditional textbook-based teaching methods make this problem even worse. This study tackles the challenge students encounter in comprehending biological taxonomy by developing Taksonify, a mobile application aimed at enhancing taxonomy education through gamification and computer vision. The ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) was used in the study. Expert validation was performed, and the application was evaluated on 35 tenth-grade students through pre-test and post-test assessments. An expert validation score of 4.73 (media) and 4.44 (content) showed that the evaluation was very likely to work. The average score went up from 16.91 (pre-test) to 20.44 (post-test), with a gain score of 0.69 (moderate). This means that comprehension improved a lot. These results show that Taksonify is a good way to learn about biological taxonomy because it helps students understand the subject much better. The use of Taksonify demonstrates the potential of mobile-based learning tools to improve science education quality, fostering greater interest and understanding of biology among secondary students. This research supports SDGs 4 (Quality Education) particularly Targets 4.1 and 4.4, by improving student learning outcomes and strengthening ICT skills. It develops innovative mobile-based, gamified, and computer vision supported learning media to enhance the effectiveness of biology education.